Essay on the influence of rejection and consequent social exclusion in the Latin American economic and social development: Ensayo sobre la influencia del rechazo y la consecuente exclusión social en el desarrollo económico y social de América Latina - Teixeira Roncon, Edelcio; Brítez de Vergara, Margarita Maria (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
This paper presents a reflection about the mutual influence of social rejection, that implicates the social exclusion in macro phenomenon and the economic development level for Latin American Societies. These societies have social characteristics as singular and heterogeneous while share others persistent characteristics: the low level of economic development and the high social rotation and stratification, with reference in economic, monetary, symbolic or other measurements in specific zone in time. In this paper intend to show how these phenomenons are related, as well the representative importance of these three variables on Latin American social and economical characteristics.